Birth of television in Uzbekistan - Yuldashev Eldar Sadikovich, (IJRDO - Journal of Social Science and Humanities Research, 2020)
The invention and development of television art is undoubtedly closed connected with scientific research. The historic facts have witnessed the influence of scientific research progress on the development of television art. In this paper, the author intends to reveal some phenomenal facts which are known by very few people, namely, the first-ever appearance of electronic television in Uzbekistan. This paper gives us some authentic and valuable historic materials for the invention and development of television set in the world. We became witnesses of a birth of the first purely electronic television in the world, in Uzbekistan and in its capital Tashkent.